Analisis Pengaruh Desain Produk, Digital Marketing, Electronic Word Of Mouth (E-WOM) Dan Kualitas Produk Terhadap Kepuasan Pelanggan Abata Printing Purwokerto - Wapiq Nur Azizah; Mukhroji (CV. ITTC INDONESIA, 2024)
This research aims to understand and test the analysis of the influence of product design, digital marketing, electronic word of mouth, and product quality on customer satisfaction at Abata Printing. The research method used in this study is quantitative. The sampling technique used is non-probability sampling with the purposive sampling method. Research data was collected by distributing questionnaires to 96 respondents online, using multiple linear regression analysis with the assistance of SPSS 24. The research results indicate that the product design variable and electronic word of mouth (e-wom) do not have a positive and significant effect on customer satisfaction. Meanwhile, the digital marketing and product quality variablea have a positive and significant effect on customer satisfaction.